Prerequisites of creation conceptual model of scenario financial planning and forecasting in railroads - Kravchenko, Olga (Skhid, 2013)
The article deals with the prerequisites of development conceptual model of financial planning and forecasting in railroads based in scenario approach. Is offered an approach to determining the structure of the conceptual model, which involves mapping processes as training and development scenario financial plans and forecasts, and so monitoring their performance and make necessary adjustments.